Study of CoTa alloy as barrier layer for Cu/low-k interconnects. (15th September 2017) - Wang, Xu; Liu, Lin-Tao; He, Peng; Qu, Xin-Ping; Zhang, Jing; Wei, Shuhua; Mankelevich, Yuri A; Baklanov, Mikhail R
Abstract: CoTa alloy films as diffusion barriers for Cu/low- k interconnects are studied. Crystalline structure, thermal stability, barrier and sealing properties on low- k dielectric of CoTa alloys with different atomic ratios between Co and Ta are studied using different techniques. It is demonstrated that CoTa alloys with proper content and thickness can be considered as candidates to act as a barrier layer for Cu/low- k interconnects with acceptable thermal stability and resistivity. However, ultralow- k organosilicate based dielectrics with k = 2.25 and pore size about 2 nm can be sealed by this barrier against penetration of neutral molecules only when the CoTa alloy thickness is larger than 3 nm. Correlation of the barrier performance with low- k pore size is demonstrated.